2005
DOI: 10.1089/jpm.2005.8.962
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Evaluation of Required Coursework in Palliative and End-of-Life Care for Medical Students

Abstract: The evaluation provides support for the conclusion that mandatory training in palliative and end-of-life care is effective, perceived to be valuable, and contributes to good palliative and end-of-life care practices in our graduates. Furthermore, the training meets a significant demand in our graduates' clinical practice: end-of-life care. However, expanded medical school emphasis and curriculum hours are still needed for palliative care topics, because preparedness in palliative care skills was perceived to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…2 Several studies have demonstrated that end-of life educational curricula and clinical training can improve medical students' knowledge and attitude toward palliative care. [3][4][5][6] Those who complete clinical rotations and courses in palliative care feel more comfortable with death and caring for dying patients. 5,7 Research on residents and fellowships show a similar result.…”
Section: Introductionmentioning
confidence: 99%
“…2 Several studies have demonstrated that end-of life educational curricula and clinical training can improve medical students' knowledge and attitude toward palliative care. [3][4][5][6] Those who complete clinical rotations and courses in palliative care feel more comfortable with death and caring for dying patients. 5,7 Research on residents and fellowships show a similar result.…”
Section: Introductionmentioning
confidence: 99%
“…5 Many training initiatives have been implemented at different points throughout undergraduate medical training. [6][7][8][9][10][11][12][13] These have included 20-hour mandatory coursework sessions 7 ; 1-day visits to a hospice 8 ; 16 hours in a community hospice 9 ; a 4-day curriculum 6,10 ; and 1 week, 2 weeks, or 3 weeks of palliative care attachments (i.e., clinical electives) during the clinical years. [11][12][13] However, there is little information available to guide medical educators in how to best incorporate the teaching of palliative care into medical curricula.…”
mentioning
confidence: 99%
“…6,7,11 Studies report that students learn about the value of hospice care, the value of empathy, the value of the doctor-patient relationship, 12 and what it means to be a doctor 13 ; acknowledge a difference between resignation and acceptance; and start to understand death as a natural event. 8 Furthermore, students describe feeling more support and having a richer experience of role modeling after training in palliative care.…”
mentioning
confidence: 99%
“…7 Mandatory training in palliative and end-of-life care is effective and perceived to be valuable. 8 In 2006, Dickinson et al 9 reported that between 1975 and 2005, the overall offerings in subjects pertaining to death and dying increased from around 70% before 2000 to 100% in 2005. Although this trend is encouraging, a need still exists for a standardized medical school curriculum in palliative care and end-of-life issues.…”
Section: Introductionmentioning
confidence: 99%